Expanding the Expression (6n^2  6n  5)(7n^2 + 6n  5)
This expression involves multiplying two trinomials. To expand it, we will use the distributive property (also known as FOIL method).
Here's how to do it:

Multiply the first terms of each trinomial: (6n^2)(7n^2) = 42n^4

Multiply the outer terms: (6n^2)(5) = 30n^2

Multiply the inner terms: (6n)(7n^2) = 42n^3

Multiply the last terms: (6n)(5) = 30n

Multiply the first term of the first trinomial by the second term of the second trinomial: (6n^2)(6n) = 36n^3

Multiply the first term of the first trinomial by the third term of the second trinomial: (6n^2)(5) = 30n^2

Multiply the second term of the first trinomial by the first term of the second trinomial: (6n)(7n^2) = 42n^3

Multiply the second term of the first trinomial by the second term of the second trinomial: (6n)(6n) = 36n^2

Multiply the second term of the first trinomial by the third term of the second trinomial: (6n)(5) = 30n

Multiply the third term of the first trinomial by the first term of the second trinomial: (5)(7n^2) = 35n^2

Multiply the third term of the first trinomial by the second term of the second trinomial: (5)(6n) = 30n

Multiply the third term of the first trinomial by the third term of the second trinomial: (5)(5) = 25
Now, add all the terms together and combine like terms:
42n^4  30n^2  42n^3 + 30n + 36n^3  30n^2  42n^3  36n^2 + 30n  35n^2  30n + 25
Simplifying the expression:
42n^4  48n^3  131n^2 + 25
Therefore, the expanded form of (6n^2  6n  5)(7n^2 + 6n  5) is 42n^4  48n^3  131n^2 + 25.